Pure Spin Transport in YIG Films with Amorphous‐to‐Crystalline Transformation - Yu, Rui; Cao, Jiefeng; Liu, Haigang; Zhu, Fangyuan; Meng, Xiangyu; Long, Zhipeng; Li, Junqin; Wang, Yong (Advanced Physics Research, 2024)
Magnetic insulators, especially Y3Fe5O12 (YIG), are considered promising candidates for spin‐based device applications due to their ultralow damping, high spin injection efficiency, and long‐distance spin propagation. However, these intriguing features are widely studied based on crystallization YIG films. Pure spin phenomena, like spin transport in YIG films with structural evolution, remain unclear. Herein, pure spin transportation is systematically investigated in the sandwich structure formed by YIG, the inserted layer‐nominal YIG (n‐YIG) with a varied crystalline structure and heavy metal Platinum (Pt). By applying ferromagnetic resonance (FMR)‐driven inverse spin Hall effect (ISHE) measurement, the detected ISHE voltage signal presented a strong correlation with the thickness of n‐YIG and its crystalline phase. A significant increasement in spin transportation is obtained for the crystallized n‐YIG via a high‐temperature annealing. These results demonstrate that pure spin current is transported availably in the structural evolution of YIG films. Furthermore, the element‐specific X‐ray absorption spectroscopy (XAS) and X‐ray magnetic circular dichroism (XMCD) spectra on the n‐YIG films showed a distinction for the crystallized n‐YIG which indicates that the spin propagation is correlated to its magnetic order. These findings are instructive for low‐dissipation spin‐based devices. A detectable spin current transport across the structural evolution of as‐grown YIG films is observed via spin pumping‐induced inverse spin Hall effect measurement. And the amplitude of the detected signal is strongly correlated to the magnetic order in the annealed YIG films which is further confirmed by X‐ray absorption spectroscopy and X‐ray magnetic circular dichroism spectra.